PENERAPAN MODEL KOOPERATIF TERINTEGRASI PENDIDIKAN KARAKTER UNTUK PEMBELAJARAN FISIKA KELAS VIII MTsN KUBANG PUTIH - Ulfa Rahmi (Universitas Negeri Padang, 2013)
The achievement of physics learning in junior high school shows an unoptimal results. There are some factors which make such as used method is still “teacher centered”, inactive student in learning because teacher only gives the materials without communication between teacher and student, at least for establishment of skill and character values. ​​Application of cooperative learning model can be used as an alternative to solve this problem. The cooperative model which integrated for character is able to improve the competence of student. This research to find out effect of cooperative model application which is integrating character education for the compenten achievement of students learning in MTsN Kubang Putih. The research type is pre-experiment by program